PERENCANAAN SUMUR RESAPAN AIR HUJAN UNTUK KONSERVASI AIR TANAH DI DAERAH PERMUKIMAN (STUDI KASUS DI PERUMAHAN RT. II, III, DAN IV PERUMNAS LINGKAR TIMUR BENGKULU) - Kurnia Iriani; Agustin Gunawan; Besperi Besperi (Universitas Bengkulu, 2019)
The increasing of development for supporting facilities in public life triggers transformation of land use and decreasing of open space for infiltration area. This causes surface flow (run-off) and some rainwater infiltrating into land. Therefore, it is necessary made a patch like the infiltration well which is used to patch and then infiltrate rainwater into soil slowly. The purpose of this research was to determine amount and construction of infiltration well. This research was executed in housing RT. II, III, and IV Lingkar Timur at Bengkulu City that hasnumber of house 153. This study used survey methods such as measuring,questionnaire/interviewing, and percolation test to obtain the required data. Based on the data and analysis of calculation according to SK SNI 03-2453-2002, was determined that for individual infiltration well, the form of infiltration well was circle with a diameter of 1 m and a depth of 3 m, while for communal infiltration well was circle with a diameter of 1.4 m and a depth of 3 m (by 92 pieces). The others alternative form for individual infiltration well was square with a width of 1.2 m and a depth of 1.5 m, while for communal infiltration well was square with a width of 1.4 m and a depth of 3 m (by 72 pieces). Construction of infiltration well according to Technical Instruction Applying Drainage Method with Environmental Concept In Residence Area (2002) was brick wall or red brick pair without plastered and among it given hole.